2017
DOI: 10.7150/ijms.22152
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells from Cryopreserved Human Dental Pulp Tissues Sequentially Differentiate into Definitive Endoderm and Hepatocyte-Like Cells in vitro

Abstract: We previously described a novel tissue cryopreservation protocol to enable the safe preservation of various autologous stem cell sources. The present study characterized the stem cells derived from long-term cryopreserved dental pulp tissues (hDPSCs-cryo) and analyzed their differentiation into definitive endoderm (DE) and hepatocyte-like cells (HLCs) in vitro. Human dental pulp tissues from extracted wisdom teeth were cryopreserved as per a slow freezing tissue cryopreservation protocol for at least a year. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…As dental tissue is considered a biomedical waste in routine dental procedures, it is gaining more attention in the field of regenerative medicine as a potential source of MSCs without imposing any ethical issues. Many dental-derived MSCs have been identified and characterized, including MSCs from human exfoliated deciduous teeth (SHED) [30][31][32], dental pulp [16,17], papilla [16], and follicle [16]. However, the properties of these MSCs present in different anatomical regions of dental tissue and their feasibility for application in future regenerative medicine still need to be investigated in greater detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As dental tissue is considered a biomedical waste in routine dental procedures, it is gaining more attention in the field of regenerative medicine as a potential source of MSCs without imposing any ethical issues. Many dental-derived MSCs have been identified and characterized, including MSCs from human exfoliated deciduous teeth (SHED) [30][31][32], dental pulp [16,17], papilla [16], and follicle [16]. However, the properties of these MSCs present in different anatomical regions of dental tissue and their feasibility for application in future regenerative medicine still need to be investigated in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…So far, MSCs have been isolated from different anatomical regions of dental tissue [15], which exhibits fibroblast like morphology, express cell surface, pluripotent markers, and differentiate into mesodermal lineages such as adipocytes, osteocytes, and chondrocytes [16]. Further, these cells possess transdifferentiation potency and they can successfully differentiate toward neuronal lineage [16], hepatocytes [17], and pancreatic cells [14]. It is considered that dental stem cells have a neural crest origin and have analogous properties to that of neural crest [18].…”
Section: Introductionmentioning
confidence: 99%
“…The term "tissue engineering" was coined by Langer and Vacanti in the early 1990s for describing the technique for biological tissue regeneration (12). Tissue engineering approach requires three main key elements (triad): Stem cells, Scaffolds (matrix) and growth factors (morphogens) (11).…”
Section: Stem Cell Based Tissue Engineering Of Dental Pulp Stem Cellsmentioning
confidence: 99%
“…The implantation of PDSLC seeded on HA/TCP is surgically created periodontal defects in miniature swine exhibited their excellent capacity to form bone, cementum, and PDL. These results hold utmost importance because of the high alarming statistics of periodontitis which is the leading cause of the tooth loss, especially in the elderly population (11). The tooth like structures can be created from biodegradable polymer scaffolds (collagen coated polyglycolic acid, calcium phosphate material, collagen sponges) seeded with dissociated single-cell suspension.…”
Section: Stem Cell Based Tissue Engineering Of Dental Pulp Stem Cellsmentioning
confidence: 99%
“…Therefore, hUSCs have great application in tissue reconstruction, disease modeling, and drug discovery. 11,12 Up to now, many experiments have shown that adult stem cells are able to be differentiated into hepatocyte-like cells or hepatocytes in vitro and in vivo, [13][14][15][16][17][18][19] and most induction methods are related to cell growth factors. 10 However, the lack of liver sources is a major impediment to these applications, furthermore, studies using human hepatocyte cell lines and animal experiments sometimes cannot reflect the real situation.…”
Section: Introductionmentioning
confidence: 99%